Unmanned aerial vehicles: potential for use in the storage systems of industrial companies - N. Yu. Barkova; E. D. Deulina; M. A. Malysheva; D. P. Kirsanova; O. A. Borodina (Вестник университета)
In the article, the authors investigate the problem of using unmanned aerial vehicles (drones) in company warehouses and consider their use as one of the ways to optimize the logistics business processes of companies. Technologies are considered, on the basis of which modern unmanned aerial vehicles, drone models of various companies, the main functionality of drone’s work. The authors high-light the strengths and weaknesses of unmanned aerial vehicles, key factors determining the success of the use of drones, and favorable conditions for their use in warehouses. The authors are considering the possibility of sharing drones and RFID technology. Barriers to the active introduction of drones into the logistics business processes of warehousing systems and requirements for warehouse complexes planning the use of unmanned aerial objects have been identified. Promising areas of application of technology in warehouse logistics are also considered: creation of anti-theft and fire protection systems, using drones to read CIS marks. The authors used data from analytical reports and data collected by the authors themselves, as well as empirical research methods.